1995
DOI: 10.1097/00001888-199506000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Gender-associated differences in matriculating and graduating medical students

Abstract: Data from the 1993 Matriculating Student Questionnaire (MSQ) and the 1994 Medical School Graduation Questionnaire (GQ) of the Association of American Medical Colleges were investigated for differences in responses between men and women. Notable differences were discovered, particularly with regard to career plans and experiences during medical school. Findings from the GQ include that a higher proportion of women rated curricular coverage of numerous subjects inadequate and that women students more frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…As to whether there are inherent differences in female perceptions as suggested in prior surveys of medical students [9,24,34] we found that despite similar curricular exposure, more women believed that the level of ethics training they received was moderate compared to men (mean male 6.04, mean female 4.88). Our observations are consistent with Bickel and Ruffin, who documented that more female medical students reported inadequate curricular coverage of many subjects compared with males [14]. Similarly, Roberts et al have reported women’s desire for more education regarding ethical dilemmas compared with their male counterparts [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As to whether there are inherent differences in female perceptions as suggested in prior surveys of medical students [9,24,34] we found that despite similar curricular exposure, more women believed that the level of ethics training they received was moderate compared to men (mean male 6.04, mean female 4.88). Our observations are consistent with Bickel and Ruffin, who documented that more female medical students reported inadequate curricular coverage of many subjects compared with males [14]. Similarly, Roberts et al have reported women’s desire for more education regarding ethical dilemmas compared with their male counterparts [17].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Roberts et al have reported women’s desire for more education regarding ethical dilemmas compared with their male counterparts [17]. This could reflect the fact that females are looking for greater exposure to ethical issues and hence value this subject more than their male counterparts [14]. Also despite the expectation that in an outcomes-based curriculum, formal ethics education would be comparable for male and female students, it is plausible that personal experiences and the clinical exposure might be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female medical students and physicians often have different attitudes than their male colleagues, and may be more inclined toward the ethic of social responsibility (Bickel and Ruffin, 1995;Crandall et al, 1993;Crandall et al, 1997;Xu et al, 1995). Upon entry into medical school, attitudes of female students toward caring for indigent patients were more favorable, and remained so throughout medical school (Crandall et al, 1993;Crandall et al, 1997).…”
Section: Gender and Attitudesmentioning
confidence: 99%
“…Based on our prior work and the existing empirical literature suggesting that ethics education is underdeveloped in many if not most medical schools, especially during the clinical training years (11,21), that women health professionals and trainees are particularly positive in endorsing the importance of ethics education and that psychiatry residents have a strong interest in ethics (22)(23)(24)(25). We generated four hypotheses: 1) medical students and residents will identify the need for greater curricular attention for most or all topics presented; 2) women respondents will express greater need than their male colleagues; 3) more advanced trainees, i.e., clinical medical students and residents, will express greater need than their preclinical student colleagues; and 4) psychiatry residents will express greater need than primary care program or other specialty program residents.…”
Section: Hypotheses and Data Analysismentioning
confidence: 99%